2016
DOI: 10.1175/mwr-d-15-0100.1
|View full text |Cite
|
Sign up to set email alerts
|

On Polarimetric Radar Signatures of Deep Convection for Model Evaluation: Columns of Specific Differential Phase Observed during MC3E*

Abstract: The representation of deep convection in general circulation models is in part informed by cloudresolving models (CRMs) that function at higher spatial and temporal resolution; however, recent studies have shown that CRMs often fail at capturing the details of deep convection updrafts. With the goal of providing constraint on CRM simulation of deep convection updrafts, ground-based remote-sensing observations are analyzed and statistically correlated for four deep convection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 95 publications
3
42
0
Order By: Relevance
“…The squall‐line MCS case simulated in this study occurred on 20 May 2011, during the Midlatitude Continental Convective Clouds Experiment (MC3E) [ Petersen and Jensen , ; Jensen et al ., ], which was supported by both the U.S. Department of Energy Atmospheric Radiation Measurement Program (ARM) and NASA's Global Precipitation Measurement mission ground validation program in north‐central Oklahoma from 22 April to 6 June 2011. Detailed ground‐based and aircraft cloud dynamical and microphysical observations are available for this case [ Mather and Voyles , ; Jensen et al ., ], which has been a focus of several recent studies [e.g., Tao et al ., , ; Giangrande et al ., ; Fan et al ., ; Kumjian et al ., ; Marinescu et al ., ; Van Lier‐Walqui et al ., ; Saleeby et al ., ; Fridlind et al ., ]. Section 2 includes a more detailed description of the case and the relevant observations used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The squall‐line MCS case simulated in this study occurred on 20 May 2011, during the Midlatitude Continental Convective Clouds Experiment (MC3E) [ Petersen and Jensen , ; Jensen et al ., ], which was supported by both the U.S. Department of Energy Atmospheric Radiation Measurement Program (ARM) and NASA's Global Precipitation Measurement mission ground validation program in north‐central Oklahoma from 22 April to 6 June 2011. Detailed ground‐based and aircraft cloud dynamical and microphysical observations are available for this case [ Mather and Voyles , ; Jensen et al ., ], which has been a focus of several recent studies [e.g., Tao et al ., , ; Giangrande et al ., ; Fan et al ., ; Kumjian et al ., ; Marinescu et al ., ; Van Lier‐Walqui et al ., ; Saleeby et al ., ; Fridlind et al ., ]. Section 2 includes a more detailed description of the case and the relevant observations used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The K DP columns (i.e., positive K DP values that are above the 0°C level) have been well studied and documented Loney et al 2002;Ryzhkov et al 2005;Kumjian et al 2010;van Lier-Walqui et al 2016). Many times, there is a spatial offset between the positive Z DR and K DP columns (Kumjian and Ryzhkov 2008), but here, they are coincident with the K DP column extending to nearly the top of the Z DR column.…”
Section: Polarimetric Variable Interpretationmentioning
confidence: 99%
“…Following the convection, stratiform, and anvil classification, radar echo is evaluated to determine whether or not signatures indicative of strong convective updrafts are present. To identify convective updrafts, the SL3D algorithm searches for three well-known radar signatures: 1) weak-echo regions [WERs; bounded or unbounded, e.g., Browning and Donaldson (1963); Musil et al (1986); Calhoun et al (2013)], 2) Z DR columns (e.g., Caylor and Illingworth 1987;Illingworth 1988;Bringi et al 1991;Conway and Zrnić 1993;Ryzhkov et al 1994;Brandes et al 1995;Loney et al 2002;Scharfenberg et al 2005;Kumjian and Ryzhkov 2008;Kumjian et al 2014), and 3) K DP columns (e.g., Zrnić et al 2001;Loney et al 2002;Kumjian and Ryzhkov 2008;Van Lier-Walqui et al 2016). WERs are elements of a convective storm with relatively low Z H values at lower altitudes that are at least partially bounded horizontally and above by relatively high Z H values.…”
Section: Convective Updraftmentioning
confidence: 99%
“…The K DP columns, on the other hand, indicate updrafts that have lofted large concentrations of moderately sized (2-4 mm) raindrops above the freezing level (e.g., Loney et al 2002). Van Lier-Walqui et al (2016) found that K DP columns are not only a good indicator of the presence of an updraft, but changes in the volume of a K DP column are correlated to changes in the updraft mass flux. Snyder et al (2015) have recently developed an algorithm for objectively identifying Z DR columns in single-radar observations.…”
Section: Convective Updraftmentioning
confidence: 99%